Strategi Komunikasi Perempuan Dalam Menghindari Cyber Crime Pada Aplikasi Dating Online Tinder - Yulistiawan, Tasyadilla Nur Azmi; Juwita, Rina (Jayapangus Press, 2024)
Along with the rapid advancement of information and communication technology, the use of online dating applications is now widely used by various groups. The use of this application is considered to help individuals find friends and even partners. One of the online dating applications that is trending among them is Tinder. With the